Assessment of anosmia/hyposmia in post-COVID-19 patients: a cross-sectional study in an eastern province of Saudi Arabia - Mohamed, Reem; Alsuhibani, Reem; Almasaoud , Heba; Alsubhi, Shahad; Alabdulazeem , Lama; Alzahrani , Nora; Alsaif, Seham; Al Ghamdi, Kholoud; Al-Asoom, Lubna (Acta Biomedica Atenei Parmensis, 2023)
Background and aim It has been shown that olfactory dysfunction is one of Coronavirus disease-2019 (COVID-19)common and puzzling symptoms that may persist weeks after the infection. This study aimed for the objective assessment of persisting olfactory dysfunction in post-COVID-19 patients. It also investigated the factors associated with the development of such symptoms in the Eastern Province of Saudi Arabia. Methods: A cross-sectional study that was conducted in the Department of Physiology, College of Medicine, Imam Abdulrahman bin Faisal University, Khobar, Saudi Arabia. One hundred and forty-seven participants were included in this study, and sixty of them agreed  to participate in the objective testing using the Connecticut Chemosensory Clinical Research Center (CCCRC) olfaction test. Results: There was a significant correlation between the following factors: (1) Persistence of anosmia/hyposmia and the time of onset of anosmia/hyposmia (P=0.015). (2) Persistence of anosmia/hyposmia and the duration of anosmia/hyposmia (P=0.012). (3) Duration of anosmia/hyposmia and the duration of COVID-19 symptoms (P=0.010). Interestingly, there was a significant association between the subjective participants’ claim of anosmia/hyposmia and the score of their objective assessment (P=0.026). Conclusion: The current study demonstrated that post-COVID-19 participants with delayed onset of anosmia/hyposmia and/or longer duration of either anosmia/hyposmia or COVID-19 symptoms were prone to have persistent olfactory dysfunction. Further studies are necessary to uncover the underlying pathophysiology and management of this olfactory dysfunction in COVID-19 patients.